إعداد المعلم كوجه من أوجه التنمية البشرية في قطاع التعليم - حميدشة, نبيل (University of Eloued جامعة الوادي, 2017)
تعتبر عملية إنتاج الأفراد من أصعب و أخطر العمليات، حيث تتولى هذه المهمة العديد من المؤسسات المجتمعية، بدء بالأسرة و وصولا إلى وسائل الإعلام و الاتصال الحديثة كالتلفزيون و الإنترنيت و غيرهما، و من بين هذه المؤسسات المحورية في إنتاج الأفراد المدرسة، هذه الأخيرة أوجدها المجتمع لتقابل حاجة من حاجاته المهمة و هي تنشئة أفراده وفق المواصفات الرسمية التي يتوافق عليها المجتمع. و منه يعتبر المعلم حجر الزاوية في عملية التنشئة المدرسية، و من تم فإنه يتولى مهمة خطيرة و شاقة تستدعي العناية به من كل الجوانب و خاصة من ناحية إعداده. هذه العملية تعتبر لب عملية التنمية البشرية في قطاع التربية و التعليم. و عليه جاءت هذه الورقة البحثية لتسلط الضوء على عملية إعداد المعلم في الفكر التربوي The process of individuals' upbringing is one of the most difficult and most dangerous operations, and this task is carried out by many community institutions, starting with the family and access to the media and modern communication such as television, the Internet and so on. Among these central institutions is the school. It was created by society to meet one of its important needs, which is to raise its members in accordance with the official specifications on which the society agrees. The teacher is considered as the cornerstone of the process of school upbringing, and whoever has been assigned a serious and arduous task requires attention from all sides, especially in terms of preparation. This process is at the core of human development in the education sector. This paper highlights the process of preparing the teacher in educational thought
Preparing the teacher as a facet of human development in the education sector
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: المعلم، الإعدادـ الموارد البشرية; teacher, preparation, human development.